‘Feels (Not) Like At Home’: Perlakuan di Lapas, Interaksi Sosial dan Harapan Pengguna Narkoba Mantan Narapidana (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
AbstractThe estimation of HIV prevalence among prisoners is 24 times higher than that of the generalpopulation in Indonesia. This high HIV prevalence in a number of prison in Indonesia is caused bythe many drug users who become prisoners (Kemenhukham2010). The existence of HarmReductionprogram in Indonesia plays a significant role in the success of the reduction in the risk ofHIV transmission through injecting among drug users. This article is focused on thesocialinteraction experienced by drug users when they are sentenced and after serving a sentence.Despite the fact that Ditjenpas declares that prisoners are entitled to obtain appropriate treatment,most drug users, particularly injecting drug users, feel that they are treated differently from otherprisoners as well as warden due to their drug users status, especially when they access healthservices. Thus, they end up learning helplessly because of their prisoner status. Drug users preferto be isolated from other non-drug user prisoners since the interaction with the latter has giventhem a chance ‘to learn’ about other kinds of criminals. Interaction among drug users themselvesis relatively fine, and they share ‘sense of togetherness’ and ‘sense of belongingness’ led to theirsecurity in the prison. But this is not the case between drug users and non-drug use prisoners. Thelatter tends to stigmatize. Family support when they are sentenced and after serving a sentence ishighly expected because family plays a significant role to help them dealing with their addictionandthe effort to get out from drug use vicious circle, particularly for their healthcare. Manysupport by their family, others are neglected. But, family can also be the one who supports theirdrug using habit in the secure atmosphere (named home) to secure family shame. When theyrelease from prison, many expect to be accepted as other members of the society and are includedin surrounding social activities. Others prefer to be socially neglected because they perceive thatothers concern potentially lead to social stigmaKeywords: drugs, ex-convict, social interaction, HIV, prisoners.